Preoperative assessment for the risk of Clavien-Dindo classification ≥ II grade complications after total parathyroidectomy without auto-transplantation in patients with secondary hyperparathyroidism - Ni, Yuanzhi; Xu, Lindi; Li, Zhenli; Li, Liang; Yan, Shihang; Cheng, Guangming; Wang, Chunhui; Tang, Yufu (Frontiers in Endocrinology, 2025)
ObjectiveComplications following total parathyroidectomy (TPTX) without autotransplantation adversely affect the prognosis of patients with secondary hyperparathyroidism (SHPT). This study aimed to identify preoperative risk factors of Clavien-Dindo grade ≥ II complications after TPTX in SHPT patients, and develop a visualized model to predict the risk of complications (≥ grade II).MethodsClinical data were retrospectively collected from SHPT patients who underwent TPTX at our center between January 2013 and March 2025. The cohort was chronologically divided into a training set (n=552) and a validation set (n=236) in a 7:3 ratio. Postoperative complication severity was assessed using the Clavien-Dindo classification system. Patients were stratified into two groups based on complication grade: a high-risk group (grade ≥II) and a low-risk group (grade <II or no complications). Independent risk factors of Clavien-Dindo grade ≥ II complications were identified through univariate and multivariate logistic regression analyses. A nomogram was developed using these independent risk factors. The performance of this model was then evaluated using the validation set.ResultsAmong 788 patients, 546 (69.3%) developed postoperative complications, including 369 cases (46.8%) of grade ≥ II complications. Multivariate analysis identified serum alkaline phosphatase, intact parathyroid hormone, serum calcium, and serum potassium as independent risk factors of grade ≥II complications. The nomogram achieved good concordance indexes of 0.826 (95% confidence interval (CI), 0.778–0.874) and 0.807 (95% confidence interval (CI), 0.739–0.874) in predicting the risk of postoperative complications (grade ≥ II) in the training and validation cohorts, respectively, with well-fitted calibration curves. Both the decision curve and the clinical impact curve indicated substantial clinical benefit provided by the nomogram.ConclusionA nomogram was developed and validated to predict complications (grade ≥ II) following TPTX without autotransplantation in patients with SHPT. This model may aid in identifying high-risk patients and informing perioperative decision-making.